Long-term plasticity in interneurons of the dentate gyrus - Ross, Stephen T. (The National Academy of Sciences, 2001)
Single interneurons influence thousands of postsynaptic principal cells, and the control of interneuronal excitability is an important regulator of the computational properties of the hippocampus. However, the mechanisms underlying long-term alterations in the input–output functions of interneurons are not fully understood. We report a mechanism of interneuronal plasticity that leads to the functional enhancement of the gain of glutamatergic inputs in the absence of long-term potentiation of the excitatory synaptic currents. Interneurons in the dentate gyrus exhibit a characteristic, limited (≈8 mV) depolarization of their resting membrane potential after high-frequency stimulation of the perforant path. The depolarization can be observed with either whole-cell or perforated patch electrodes, and it lasts in excess of 3 h. The long-term depolarization is specific to interneurons, because granule cells do not show it. The depolarization requires the activation of Ca(2+)-permeable α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA) receptors and the rise of intracellular Ca(2+), but not N-methyl-d-aspartate (NMDA) receptor activation. Data on the maintenance of the depolarization point to a major role for a long-term change in the rate of electrogenic Na(+)/K(+)-ATPase pump function in interneurons. As a result of the depolarization, interneurons after the tetanus respond with action potential discharges to previously subthreshold excitatory postsynaptic potentials (EPSPs), even though the EPSPs are not potentiated. These results demonstrate that the plastic nature of the interneuronal resting membrane potential underlies a unique form of long-term regulation of the gain of excitatory inputs to γ-aminobutyric acid (GABA)ergic neurons.